Nos sumus tempora : studies on Augustine and his reception offered to Mathijs Lamberigts - Dupont, Anthony; François, W. (Wim); Leemans, Johan, 1965- (Bibliotheca Ephemeridum theologicarum Lovaniensium, 2020)
Mathijs Lamberigts' long and prolific research career started with the study of the controversy between Julian of Aeclanum and Augustine of Hippo on the issues of human free will and divine grace. This research interest rapidly came to include all aspects of the turbulent life, the massive oeuvre, and the complex ideas of the doctor gratiae, imbedded in the historical, political, socio-economic, religious, ecclesial, and intellectual context of the fourth and fifth centuries. Driven by a deep respect for the original sources, and always well informed about the established scholarship, Lamberigts deployed a rigorous historical-critical method in his publications. These twenty-seven papers are offered to Mathijs Lamberigts by former students and colleagues, out of gratitude for his generous personality, for his inspiring scholarship, and for his academic leadership.